Utilizing Strategy-Based Instruction on The EFL Listening Achievement: A Quasi- Experimental Study - Ika Hidayanti; Eko Suhartoyo; Kurniasih (JEELS (Journal of English Education and Linguistics Studies), 2020)
The current study aims at investigating the effectiveness of using strategy-based instruction on the studentâ€™s listening achievement. This research applied quasi-experimental design, and the instruments were pretest and posttest. Both tests were about putting the pictures in order and form completion. Â Prior to strategy choice, this study utilized Posteriori Taxonomy of Strategies of Learning English Listening Skill (Zuhairi & Hidayanti, 2014) especially focusing on the use of eight strategy categories deployed by successful students (Hidayanti & Umamah, 2018). Gaining the result from Independent t-Test analysis, it was found out that the experimental group outperformed better than their counterparts in control group. Thus, Strategy-based instruction plays important role to enhance and improve the EFL learnersâ€™ listening skill.